Size and Returns: A Study of the Indian Stock Market - Prasad, Saroj S.; Verma, Ashutosh (Indian Journal of Finance, 2013)
The Size effect is one of the prominent anomalies which have been observed in the stock markets around the world. The present study attempts to find out if the portfolio of small stocks yields higher returns vis-a-vis the portfolio of large stocks and whether the size effect is present in the Indian stock market or not. The sample consists of the monthly returns of the stocks included in the S&P CNX 500 index from April 1, 2001 to March 31, 2010. Equal weighted portfolios of thirty smallest and largest stocks were constructed for each year for the entire period of the study based on the criteria of total assets and market capitalization. Using correlation analysis, CNX Nifty Junior was finalized as the market proxy, and the market model was applied by using the variables of excess returns on the portfolio of the stocks and the returns on the market proxy. The results indicate that the returns on the portfolio of small stocks are not significantly different from the returns on the portfolio of large stocks. Therefore, based on the results, the study concludes that the size effect is not present in the Indian stock market.